Isovaleric acidemia in a neonate presenting as sepsis and diabetic ketoacidosis: A case report (Indian Journal of Case Reports, 2020)
Isovaleric acidemia (IVA), an inborn error of leucine catabolism resulting in the accumulation of derivatives of isovaleryl-CoA that leads to hyperammonemia and ketoacidosis. IVA is clinically characterized by lethargy, vomiting, and a distinctive smell of “sweaty feet.” We report the case of a 10-day-old male neonate who presented with acute encephalopathy, hyperglycemia, increased anion gap metabolic acidosis, ketosis, and features of sepsis. After the management of acute metabolic decompensation, he was successfully treated with dietary restriction of leucine and L-carnitine supplementation. This case is of interest because of the rarity of presentation, early detection, and prompt implementation of the treatment with satisfactory outcomes.